(untitled) (Journal of Governance and Development (JGD), 2025)
The paper examines the impediments associated with effective social service delivery in the Gongulong community, a conflict-affected area in Jere, Borno State, Nigeria. The paper focuses on training and development gaps among social workers in the Gongulong community. The paper adopted a survey design and collected data from 200 social workers who were randomly selected. These workers were selected from Non-Governmental Organizations (NGOs), government organizations, and independent practitioners. A structured questionnaire was utilized in the data collection, and the data was analyzed using descriptive statistics. The data identified the existing competencies, challenges, and professional development needs among social workers in the Gongulong community. Findings from the study identified significant gaps in key areas of social work practice, including counseling, ethical decision-making, case management, report writing and crisis intervention. Many of the participants reported low proficiency in these areas, which highlights a critical training and development need. Many limitations to accessing professional development and training were identified in this paper, including lack of organizational support, the existence of time constraints, and limited funding. The social workers expressed a strong interest in advanced degree opportunities, mentorship programs, and in-person workshops in terms of preferred training types. The relevance of continuous professional development and training that would enhance the skills and confidence of social workers in conflict-affected areas has been underscored by the paper. The paper’s findings equally stress the institutionalization of context-specific professional development and training initiatives that may address peculiar community needs and emerging challenges in social work practice. The paper recommended targeted training and context-specific capacity building, collaborative learning and technology-enhanced training, and organizational and financial support for professional development.